Practices and perspectives in wound management in Primary Health Care: An exploratory analysis in the context of public health (Research, Society and Development, 2025)
The aim of this study was to explore clinical practices, the impact of the use of innovative technologies and the perception of health professionals in the management of wounds in Primary Health Care (PHC). Using a qualitative approach based on a narrative bibliographic review, the research analyzed scientific articles, books and technical documents, based on the descriptors: “Primary Health Care”, “dressings”, “hydrogel dressings” and “professional training”. The results showed structural limitations, such as insufficient specialized materials and low patient adherence to prolonged treatments. The potential of advanced technologies, such as bioactive dressings and telemonitoring tools, to optimize care was highlighted. The conclusion is that wound management in PHC requires interdisciplinary models based on scientific evidence and allied to inclusive public policies, promoting improvements in the quality of care and in patients' lives.